Uptake of genetic testing and long-term tumor surveillance in von Hippel-Lindau disease - Chávez Mireya; Rodríguez Yaneth; Sosa Ana-Luisa; Yescas Petra; Familiar Itziar; De Biase Irene; Ochoa Adriana; Alonso Elisa; Rasmussen Astrid; López-López Marisol; Bidichandani Sanjay I (BMC, 2010)
Abstract Background von Hippel-Lindau (VHL) disease is a hereditary cancer syndrome caused by germline mutations in the VHL gene. Patients have significant morbidity and mortality secondary to vascular tumors. Disease management is centered on tumor surveillance that allows early detection and treatment. Presymptomatic genetic testing is therefore recommended, including in at-risk children. Methods We tested 17 families (n = 109 individuals) for VHL mutations including 43 children under the age of 18. Personalized genetic counseling was provided pre and post-test and the individuals undergoing presymptomatic testing filled out questionnaires gathering socio-demographic, psychological and psychiatric data. Mutation analysis was performed by direct sequencing of the VHL gene. Mutation-carriers were screened for VHL disease-related tumors and were offered follow-up annual examinations. Results Mutations were identified in 36 patients, 17 of whom were asymptomatic. In the initial screening, we identified at least one tumor in five of 17 previously asymptomatic individuals. At the end of five years, only 38.9% of the mutation-carriers continued participating in our tumor surveillance program. During this time, 14 mutation carriers developed a total of 32 new tumors, three of whom died of complications. Gender, education, income, marital status and religiosity were not found to be associated with adherence to the surveillance protocol. Follow-up adherence was also independent of pre-test depression, severity of disease, or number of affected family members. The only statistically significant predictor of adherence was being symptomatic at the time of testing (OR = 5; 95% CI 1.2 - 20.3; p = 0.02). Pre-test anxiety was more commonly observed in patients that discontinued follow-up (64.7% vs. 35.3%; p = 0.01). Conclusions The high initial uptake rate of genetic testing for VHL disease, including in minors, allowed the discontinuation of unnecessary screening procedures in non mutation-carriers. However, mutation-carriers showed poor adherence to long-term tumor surveillance. Therefore, many of them did not obtain the full benefit of early detection and treatment, which is central to the reduction of morbidity and mortality in VHL disease. Studies designed to improve adherence to vigilance protocols will be necessary to improve treatment and quality of life in patients with hereditary cancer syndromes.